Between exacerbation and alleviation? - Tom O’Regan (Communicare)
Problems of social transformation and inclusiveness are not just social problems, they are also media communication problems; and they are not just South African problems they are internationally shared. The same widening gap between rich and poor, the uneven and often skewed benefits of globalisation, and political disruption all sit alongside and intersect with a changing communication environment. While both our media content and our ways of paying for media are stable, the ends they serve and the communication instruments to which they are attached are mutating. In an era of connectivity, both social media and new content priorities are recalibrating our understanding of media, producing both new uses for media and new regimes of knowledge about media alike. Assessing the social and political significance of these changes becomes all the more urgent when we consider that social transformation and inclusiveness will increasingly need to work through these new communication settings.